El Impacto de la Accesibilidad en el Derecho a la Vida Privada y Familiar - Begoña Rodriguez Diaz (European Papers, 2023)
(Series Information) European Papers - A Journal on Law and Integration, 2023 8(2), 525-535 | European Forum Insight of 3 August 2023 | (Table of Contents) I. Introducción - II. Hechos - III. La falta de accesibilidad como límite al derecho a la vida privada y familiar - IV. Accesibilidad y ajustes razonables: una oportunidad perdida - V. La carga desproporcionada e indebida - VI. Conclusión | (Abstract) Persons with disabilities keep struggling to enjoy their rights on equal conditions with other people de-spite being granted the right of non-discrimination under several international treaties. The European Court of Human Rights (ECtHR) is increasingly turning to a systemic interpretation of the European Convention on Human Rights with the United Nations Convention on the Rights of the Persons with Disabilities (CRPD). However, the case to be studied shows some contradictions between the interpre-tation given by the ECtHR and the Committee of the CRPD and points to the need of a better under-standing of notions related with disability and a stricter control on the States’ discretion to adopt rea-sonable accommodation measures.